Investigation of Intravenous Zoledronic Acid Therapy on Circulating Lymphocyte Subpopulation in Patients with Primary Osteoporosis: A Pilot Study - Min Cui, Ph. D; Na Zhang, M.Med; Gang Zhang, B. Med; Lei Han, M.Med; Ling Zhi Yu, Ph. D (Elsevier, 2021)
ABSTRACT: Background: Several studies have investigated the immunomodulating properties of zoledronic acid on T lymphocytes, but the causal relationship between the function of T cells and the efficacy of zoledronic acid has not been elucidated Objective: To investigate the causal relationship between the function of zoledronic acid and T cells. Methods: We conducted an observational perspective study to observe the effect of intravenous zoledronic acid once yearly for 2 years on lymphocyte subsets in patients with primary osteoporosis through observing the blood cells analysis and the level of lymphocyte subpopulations before and on day 1, 2, and 3 after first and second administration of intravenous zoledronic acid and bone mineral destiny 1 year after a single administration of zoledronic acid. Results: White blood cell count and neutrophils increased, whereas lymphocytes and eosinophils decreased after the first and second zoledronic acid infusion. The count of CD3+T cells, CD3+CD4+T cells, and CD16+CD56+ natural killer lymphocytes decreased from day 1 to day 3 after the first and second zoledronic acid infusion, but the results of second infusion showed no significance. Conclusions: Further, larger size, more in-depth studies are indicated to examine whether the short-term changes in white blood cells and lymphocyte subtypes noted after 2 once-yearly zoledronic acid injections in this small population of adult patients is associated with the stimulation of immune mechanisms. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)